Intensive Care Unit Staff and Resource Utilization: Is It an Effective Factor? - Majid Golestani Eraghi; Mohammad Taghi Beigmohammadi; Ali Akbar Soleimani; Mojtaba Mojtahedzadeh (Tehran University of Medical Sciences, 2013)
The aim of present study was to determine the impact of two different ICU management model, open and semi closed, on resources utilization in intensive care unit.Retrospective cohort analysis using data from hospital database was applied to compare the effect of ICU management model on ICU length of stay and bed disposition of 1064 patients admitted to the general ICU of Imam Khomeini Hospital of Tehran, Iran during the two consecutive 12-month periods from Mar, 2009 to Feb, 2010.In open and semi closed interval 380 and 684 patients were admitted to ICU respectively. There was no significant difference in age, gender and severity of illness (based on APACHE-II score) and nurse to bed ratio between two groups. Average ICU length of stay, net mortality rate and bed turnover rate were lower in semi closed model than open model management significantly (P